Analysis of Regency and City Government Financial Reports in Provinsi Nusa Tenggara Barat - Utami, Nadhirah Apsari; Martiningsih, Rr. Sri Pancawati (East Asian Journal of Multidisciplinary Research, 2024)
This research aims to analyze the financial condition of district and city governments in West Nusa Tenggara Province for the 2017-2021 period using analysis of financial flexibility ratios, financial independence ratios, and solvency ratios. The type of research used is descriptive quantitative. The research results show that for the group of district and city governments in West Nusa Tenggara Province in the 2017-2021 period that showed the best conditions in the short-term financial solvency dimension was the Bima City Government; the dimension of long-term financial solvency is the Bima Regency Government; the budget solvency dimension is the North Lombok Regency Government; the operational solvency dimension is the North Lombok Regency Government; the dimension of financial independence is the Mataram City Government; the financial flexibility dimension is the West Sumbawa Regency Government; the dimension of service solvency is the West Sumbawa Regency Government.